Islam Hadhari Menjana Kemajuan Ummah - Safei, Su'aidi (2005)
Islam Hadhari approach emphasizes on the development of civilization based on Islamic worldview. It adopts the principles of moderation, of a practical and realistic, balanced approach in all aspects, stimulate toward a change in mindset, comprehensive, systematic and non-partisan.